2010
DOI: 10.1007/s00404-010-1541-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of MRI for selecting patients with endometrial cancer and significant co-morbidities for vaginal hysterectomy

Abstract: The risk of adnexal metastasis is less than 1% in clinically early stage disease and highly unlikely if MRI suggests that the disease is confined to the inner half of the myometrium and low-grade disease. MRI has a high specificity and negative predictive value in endometrial cancer staging with reduced sensitivity of detecting cervical, adnexal and lymphatic spread. We suggest that vaginal hysterectomy might be a safe alternative to laparotomy in the treatment of radiological early stage disease in medically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…3D-TVS cannot predict lymph node metastases. Previous studies have reported the sensitivity of MRI to be 46–56% and the specificity to be 88–95% [17,18]. Our study shows that in predicting LNM, the sensitivity, specificity, PPV, NPV, and accuracy of MR were 58%, 96%, 63%, 95%, and 92.43% respectively.…”
Section: Discussionsupporting
confidence: 56%
“…3D-TVS cannot predict lymph node metastases. Previous studies have reported the sensitivity of MRI to be 46–56% and the specificity to be 88–95% [17,18]. Our study shows that in predicting LNM, the sensitivity, specificity, PPV, NPV, and accuracy of MR were 58%, 96%, 63%, 95%, and 92.43% respectively.…”
Section: Discussionsupporting
confidence: 56%
“…MRI is recommended for the initial staging and report of endometrial cancer [493][494][495][496] and preoperative pelvic MRI is a moderately sensitive and specific method of identifying invasion to the outer half of myometrium in endometrial cancer [497][498][499]. MRI has a high specificity and negative predictive value in endometrial cancer staging [500]; however, its accuracy in detecting myoinvasion is limited [501]. MRI with DWI and DCE sequences can help establish a correct diagnosis [502,503], while 3.0 T multimodal MRI is an important imaging tool for preoperative endometrial cancer staging [504].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…A retrospective cohort study reported that MRI has a high specificity (93%) and NPV (92%) in endometrial cancer staging with reduced sensitivity (56%) of detecting cervical, adnexal, and lymphatic spread. 6 In the evaluation of cervical involvement, Vasconcelos et al 7 reported that the MR sensitivity for cervical extension was 61%, whereas Celik et al 8 reported that the accuracy rate for MRI was 92.2% and for frozen sectioning 95.5%. Recently, some reports have shown that MRI has limited usefulness in endometrial cancers.…”
Section: Discussionmentioning
confidence: 99%